Human social genomics: Concepts, mechanisms, and implications for health - George M. Slavich; Summer Mengelkoch; Steven W. Cole (Wiley, 2023)
Abstract The exciting field of human social genomics provides an evolutionarily informed, multilevel framework for understanding how positive and negative social-environmental experiences affect the genome to impact lifelong health, well‐being, behavior, and longevity. In this review, we first summarize common patterns of socially influenced changes in the expression of pro‐inflammatory and antiviral immune response genes (e.g., the Conserved Transcriptional Response to Adversity), and the multilevel psychological, neural, and cell signaling pathways by which social factors regulate human gene expression. Second, we examine how these effects are moderated by genetic polymorphisms and the specific types of social-environmental experiences that most strongly affect gene expression and health. Third, we identify positive psychosocial experiences and interventions that have been found to impact gene expression. Finally, we discuss promising opportunities for future research on this topic and how health care providers can use this information to improve patient health and well‐being.